Reason and responsability - Díaz Ardila, Jorge Aurelio (Estudios de Filosofía, 1992)
The article is a defense of Spinoza's conception of Freedom and of its importance for contemporary ethical discussion. Critical elements are XVIIth Century rationalistic proposals, XVIIIth Century ethical formalism and Horkheimer and Adorno's distortion of Spinoza.